DIFFERENT APPROACHES TO THE UNDERSTANDING OF LAW AND THE SIGNIFICANCE OF THESE APPROACHES IN THE FIELD OF LEGAL SCIENCE - Ashuroxunova Iroda Tohir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article discusses different approaches to understanding law, their differences and common aspects, and the significance of these approaches in the field of legal science..